Intertidal Biogeographic Subprovinces: Local and Regional Factors Shaping Fish Assemblages - Andrades, Ryan; Machado, Fabíola Seabra; Reis-Filho, José Amorim; Macieira, Raphael M.; Giarrizzo, Tommaso (Frontiers in Marine Science, 2018)
Intertidal zones shelter a wealth of species and natural resources, provide important ecological services, and sustain several economic activities in coastal communities. However, the tidepool fish species that inhabit the intertidal zone are subject to a wide array of impacts due to the human presence and their accessibility, creating a challenge for the mitigation of habitat loss, in particular in tropical regions where the ecology and distribution of species are poorly known. In this study, we investigated tidepool fish species distribution patterns systematically across ca. 4,900 km of tropical Brazilian coastline (00–21° latitude) in order to verify the latitudinal trends and environmental variables influencing tidepool communities. A total of 5,113 fish specimens belonging to 67 taxa were collected at the 19 sites, revealing four distinct biogeographic subprovinces: Amazon Estuary (AE), Northern Mangrove (NM), Northeastern Semiarid (NS), and Tropical Warm (TW). Distance-based linear modeling evidenced in sequence water salinity, tidal range, shape of rocky shore formation, algae cover, distance to subtidal zone, latitude and rainfall as the most important environmental variables to shape biogeographic subprovinces. Fish species such as Bathygobius soporator, Bathygobius geminatus, Labrisomus nuchipinnis, and Scartella cristata presented wide distribution, occupying more than one subprovince. The trophic structure of the tidepool fishes also varied among subprovinces, with carnivores being associated with the AE subprovince, omnivores with the NM, and herbivores dominating the NS and TW. These findings reinforce the determining role of local and regional factors in the geographic distribution of fish and, in particular, highlight a new arrangement for the intertidal subprovinces of the tropical Brazilian shoreline, which may provide a valuable tool for the more effective management and conservation of this vulnerable ecosystem at the land-ocean interface.